2020
DOI: 10.1021/acs.jafc.0c02901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deficit Irrigation, Rootstock, and Roasting on the Contents of Fatty Acids, Phytoprostanes, and Phytofurans in Pistachio Kernels

Abstract: Pistachio (Pistacia vera L.) is a drought-tolerant species grown under the semiarid conditions of the Mediterranean basin. For this reason, it is essential to make an exhaustive quantification of yield and quality benefits of the kernels because the regulated deficit irrigation will allow significant water savings with a minimum impact on yield while improving kernel quality. The goal of this scientific work was to study the influence of the rootstock, water deficit during pit hardening, and kernel roasting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Numerous studies have shown a link between oxidative stress in plants and phytoprostane or phytofuran levels. These metabolites are excellent biomarkers capable of reporting particular environmental conditions (Figure 6): lack of water, [128] high temperatures, [120] the environment pollution [129,130] . In the case of monitoring plants in cultivation, the quantification of oxylipins would be relevant to identify changes in crops and managed cultivation efficiency [120] .…”
Section: Targeted Lipidomic For the Quantification Of Non‐enzymatic O...mentioning
confidence: 99%
“…Numerous studies have shown a link between oxidative stress in plants and phytoprostane or phytofuran levels. These metabolites are excellent biomarkers capable of reporting particular environmental conditions (Figure 6): lack of water, [128] high temperatures, [120] the environment pollution [129,130] . In the case of monitoring plants in cultivation, the quantification of oxylipins would be relevant to identify changes in crops and managed cultivation efficiency [120] .…”
Section: Targeted Lipidomic For the Quantification Of Non‐enzymatic O...mentioning
confidence: 99%
“…Phytoprostanes and phytofuranes, products of heat-treated polyunsaturated fatty acid oxidation, are bioactive compounds related to beneficial effects in both humans and plants [ 61 ]. In pistachios ( Pistacia vera L.), phytoprostanes increased under moderate stress but decreased under severe stress, showing similar contents as fruits under control conditions [ 61 ]. This decrease under severe conditions could be explained by a decrease in these compounds when their concentration reaches a threshold as stress increases.…”
Section: Drought Stressmentioning
confidence: 99%
“…This decrease under severe conditions could be explained by a decrease in these compounds when their concentration reaches a threshold as stress increases. The phytofurane total content was similar in plants under moderate stress compared with controls but decreased with severe stress [ 61 ].…”
Section: Drought Stressmentioning
confidence: 99%
See 2 more Smart Citations